Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.2 - Negative Exponents and Scientific Notation - Exercise Set: 7

Answer

$\frac{5}{6}$

Work Step by Step

We know that $a^{−n}=\frac{1}{a^{n}}$ and $\frac{1}{a^{-n}}=a^{n}$ (as long as a is a nonzero real number and n is an integer). Therefore, $3^{-1}+2^{-1}=\frac{1}{3}+\frac{1}{2}=\frac{1\times2}{3\times2}+\frac{1\times3}{2\times3}=\frac{2}{6}+\frac{3}{6}=\frac{2+3}{6}=\frac{5}{6}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.